Higenamine Attenuates Doxorubicin-Induced Cardiac Remodeling and Myocyte Apoptosis by Suppressing AMPK Activation - Jin, Cuiliu; Chai, Yu; Hu, Zhimin; Tian, Wencong; Ling, Wang; Li, Jing; Wu, Meiping (Frontiers in Cell and Developmental Biology, 2022)
Background: As an effective antitumor drug, doxorubicin (DOX) is primarily used to treat solid tumors and hematologic malignancies. However, increasing evidence has emerged indicating its cardiotoxicity, and few solutions have been proposed to counter this side effect. Higenamine (HG) is a natural compound widely found in many Chinese herbs and also serves as a component in many healthcare products. Several studies have demonstrated its cardioprotective effect in different models, but little is known about the underlying influences of HG against myocardial damage from DOX-induced chronic cardiotoxicity. Methods and Results: C57BL/6 mice and neonatal rat ventricular cardiomyocytes (NRVMs) were used to evaluate the cardioprotective effect of HG against DOX-induced myocardial damage. In mice, DOX (intraperitoneally injected 5 mg/kg every 3 days for 4 weeks) significantly increased cardiomyocyte apoptosis, cardiac atrophy, and cardiac dysfunction, which were significantly attenuated by HG (intragastrically administered with 10 mg/kg every day for 4 weeks). In NRVMs, DOX (3 μM for 24 h) significantly increased cell apoptosis and the level of reactive oxygen species while reducing the level of superoxide dismutase and mitochondrial membrane potential. Remarkably, HG can reverse these pathological changes caused by DOX. Interestingly, the protective effect of HG on DOX-induced cardiotoxicity was independent of the activation of the beta-2 adrenergic receptor (β2-AR), known for mediating the effect of HG on antagonizing ischemia/reperfusion-induced cardiac apoptosis. Furthermore, HG attenuated the abnormal activation of phosphorylated adenosine-activated protein kinase (AMPK). Consistently, AMPK agonists (AICAR) can eliminate these pharmacological actions of HG. Conclusion: Collectively, our results suggested that HG alleviated DOX-induced chronic myocardial injury by suppressing AMPK activation and ROS production.